2019
DOI: 10.1016/j.celrep.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

VCP Machinery Mediates Autophagic Degradation of Empty Argonaute

Abstract: Highlights d The empty state of Drosophila Ago1 is degraded by autophagy d Empty Ago1 is recognized by VCP, a mediator for selective autophagy d The Ufd1-Npl4 heterodimer links empty Ago1 and VCP d VCP-Ufd1-Npl4 machinery ensures proper gene silencing by microRNAs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 105 publications
1
22
0
Order By: Relevance
“…AGO1 degradation has been reported to be controlled by selective autophagy (Kobayashi et al 2019 ; Li et al 2019 ; Michaeli et al 2019 ). The P0 viral suppressor of Polerovirus is thought to trigger autophagic AGO1 degradation (Michaeli et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…AGO1 degradation has been reported to be controlled by selective autophagy (Kobayashi et al 2019 ; Li et al 2019 ; Michaeli et al 2019 ). The P0 viral suppressor of Polerovirus is thought to trigger autophagic AGO1 degradation (Michaeli et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the drug MLN4924, which blocks the activity of CULLIN-based E3 ubiquitin ligases, had a more pronounced effect in blocking AGO1 degradation highlights the importance of ubiquitylation in this process. Since both E64d and CB-5083 significantly prevented AGO1 decay, we assume that FBW2 promotes AGO1 vacuolar degradation, via a pathway involving CDC48, which could be similar to the mechanism described in flies (Kobayashi et al, 2019b). Elucidating the molecular and cellular determinants of this pathway will represent an important goal in the future.…”
Section: Mechanism Of Fbw2-mediated Ago1 Degradationmentioning
confidence: 78%
“…In animal cells, AGOs have been shown to undergo proteasomal degradation (Johnston et al, 2010) (Chinen and Lei, 2017) (Han et al, 2020) (Shi et al, 2020), but also degradation via lysosomes or even selective autophagy (Gibbings et al, 2012) (Martinez and Gregory, 2013). Interestingly, at least in Drosophila S2 cells, recent work elucidated a novel pathway in which valosin-containing protein (VCP/p97/Cdc48) directs degradation of ubiquitylated empty Ago1 through the Ufd1-Npl4 adaptor subunits (Kobayashi et al, 2019b). In Arabidopsis, our pharmacological approach revealed that the proteasome is not the main route for FBW2-mediated AGO1 decay, though a small fraction of AGO1 undergoes FBW2-dependant proteasomal degradation as supported by a slight stabilisation of AGO1 protein and the appearance of a cleavage product in the presence of Bortezomib, as well as a significant enrichment of proteasomal subunits in the FBW2 IP.…”
Section: Mechanism Of Fbw2-mediated Ago1 Degradationmentioning
confidence: 99%
“…P1/HC-Pro of TuMV speci cally primes posttranslational AGO1 degradation AGO1 degradation has been reported to be controlled by selective autophagy (Kobayashi et al, 2019;Li et al, 2019;Michaeli et al, 2019). The P0 viral suppressor of Polerovirus is thought to trigger autophagic AGO1 degradation (Michaeli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%